The Role of MSME Product Innovation in Enhancing Competitiveness, Economic Independence, and Family Welfare in the Creative and Digital Economy Era - Sudirjo, Frans; Suparwata, Dewa Oka; Irjanto, Bambang (PT. LITERASI SAINS NUSANTARA, 2025)
This study aims to analyze the role of MSME (Micro, Small, and Medium Enterprises) product innovation in enhancing competitiveness, economic independence, and family welfare in the era of the creative and digital economy. The method employed is a literature review with a qualitative approach, primarily focused on enriching references related to community service. Data were obtained from scholarly articles on Google Scholar and credible websites covering the period 1962–2025. Out of a total of 50 articles retrieved, only 24 were selected through a rigorous screening process based on relevance and quality. Analysis was conducted descriptively by examining relevant theories, previous studies, and real-world case studies of MSMEs in Indonesia. The findings indicate that product innovation plays a strategic role in creating competitive advantages, strengthening economic independence through the utilization of local resources, and improving family welfare of entrepreneurs through income growth and business sustainability. These findings confirm that product innovation not only impacts business success but also serves as an essential instrument in community service programs to reinforce the role of MSMEs as drivers of the creative and digital economy.